Labor economics - Borjas, George J. (New York McGraw Hill LLC, 2024)
Labor Economics, ninth edition by George J. Borjas provides a modern introduction to labor economics, surveying the field with an emphasis on both theory and facts. Labor Economics is thoroughly integrated with the adaptive digital tools available in McGraw-Hill$1 (Bs Connect, proven to increase student engagement and success in the course. All new Data Explorer questions using data simulation to help students grasp concepts Materials are fresh and up to date by introducing and discussing the latest research studies where conceptual or empirical contributions have increased our understanding of the labor market. The book has undergone Diversity, Equity, and Inclusion reviews to implement content around topics including generalizations and stereotypes, gender, abilities/disabilities, race/ethnicity, sexual orientation, diversity of names, and age.s
Keywords: Labor market; Labor supply; Labor demand